Instant Places: Using Bluetooth for Situated Interaction in Public Displays - Jose, Rui; Otero, Nuno; Izadi, Shahram; Harper, Richard (Pervasive Computing, 2008)
Public digital displays are increasingly pervasive and an important enabling technology for many types of ubiquitous computing scenarios. Not only do they provide a simple and effective way of bringing digital information into our physical world, but their presence could also be a catalyst for situated interaction and the emergence of local user-generated content. This paper explores the role of presence, particularly as enabled by Bluetooth device discovery, as the driver for the system's behavior and its situational awareness.